Parallel evolution of novelties: extremely long intromittent organs in the leaf beetle subfamily Criocerinae. Issue 4 (30th April 2013) - Matsumura, Yoko; Machida, Ryuichiro; Wipfler, Benjamin; Beutel, Rolf G.; Yoshizawa, Kazunori
ABSTRACT Extreme elongation of a part of the intromittent organ, the flagellum, has occurred several times in Criocerinae (Chrysomelidae). These leaf beetles have acquired a specialized pocket to store the flagellum in the abdominal cavity, at the same time allowing a quick control of movements of this structure during copulation. We investigated the morphogenesis of the intromittent organs of species with and without a flagellum to discuss the evolutionary background of parallel evolution of novel structures. We found that the specialized pocket is formed by the invagination of an epidermal layer and a resultant rotation of the primary gonopore. Invagination itself is a well‐known phenomenon in morphogenetic processes, which leads us to hypothesize that the novelty is formed by co‐opting a previously acquired genetic system. A large open‐space is present within the intromittent organ during the entire morphogenesis in species without a flagellum, and the invagination in the species with a flagellum grows in the corresponding area. This means that there are no physical impediments for the growth of a large pocket. In addition the sites of muscular attachments in the species with a flagellum are also different from those without it. The differentiation of muscles is completed immediately before adult emergence, which means the muscles are adjustable during the entire morphogenesis in this group. Simple modifications probably based on a co‐option of previously acquired genetic systems, the potential space for adding a new element, and an adjustable factor in morphogenesis of the intromittent organ facilitate the parallel evolution of the extreme elongation.